An Iteration Restoration Technique Of An Image Sequence - Fadhel, Ebtesam; Muhsin, Israa; Abed–AL-Rizak, Ban (Iraqi Journal of Science, 2024)
This paper presents a new iterative Image Restoration based on the least-Squaremethod. Based on adaptive this filtration algorithm is focused on transformation thegiven restoration model from the spatial domain to the Fourier domain. Thisimplementation of derived models needs less storage capacity and far less time inexecution. Also in this paper present ANew three Step Search for motion estimationtechnique (NTSS).In this paper two goal have been achieved, once obtained arestored image without adopted restoration technique on it (B-frame), also achieveda good rate of compression ratio by adopted motion estimation technique.